AB0422 1, 25-dihydroxyvitamin D3 modulates T cells differentiation and impacts on the production of associated-cytokines from chinese han patients with early rheumatoid arthritis. (15th June 2017) - Wen, H; Li, X
Abstract : Background: Recent studies have suggested that vitamin D may play a role in select inflammatory diseases including rheumatoid arthritis (RA). Epidemiological studies suggest that there is an association between vitamin D deficiency and susceptibility to RA. The present study sought to investigate effects of 1, 25-dihydroxyvitamin D3 (1, 25(OH)2D3) on T cells differentiation and associated cytokines in Chinese Han patients with early rheumatoid arthritis (RA). The results reported that 1, 25(OH)2D3 inhibits the synthesis of Th1 cytokines IFN-γ, Th17 cytokines IL-17, IL-22, IL-6, TNF-α, and up-regulates Th2 cytokine IL-4, which indicated that the possible immunoregulatory role and bone-sparing effects of 1, 25(OH)2D3 in RA through modulation of the Th1/Th17 and Th2 cytokine balance. Objectives: To study effects of 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ) on T cells differentiation and associated cytokines in patients with early rheumatoid arthritis (RA). Methods: The level of Th1, Th2, Th17 and Treg cell were detected with BDFACS Calibur flow cytometer. IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10, IL-17 and IL-22 were examined in 54 patients with incipient RA using a cytometric bead array (CBA). Results: After 72 hours of incubation of peripheral blood mononuclear cells (PBMCs) with 1, 25(OH)2 D3 in RA patients, the levels of IFN-γ, TNF-α, IL-2, IL-6 and IL-17 significantly decreased compared to those of the control. 1, 25(OH)2 D3 had no significantly impact on the levels of IL-4, IL-10 and IL-22. The levels of Th17 and the ratio of Th17/Treg significantly decreased in 1, 25(OH)2 D3 treated groups compared to those of the control. 1, 25(OH)2 D3 had no significantly impact on the level of Th1, Th2, Treg and the ratio of Th1/Th2. Conclusions: The present study demonstrated that 1, 25(OH)2 D3 inhibits the synthesis of Th1 cytokines IFN-γ, Th17 cytokines IL-17, IL-22, IL-6, TNF-α, and up-regulates Th2 cytokine IL-4, which indicated that the possible immunoregulatory role and bone-sparing effects of 1, 25(OH)2 D3 in RA through modulation of the Th1/Th17 and Th2 cytokine balance. References: Smolen JS, Aletaha D, McInnes IB. Rheumatoid arthritis. Lancet 2016 May 3. pii: S0140-6736(16)30173-8. doi: 10.1016/S0140-6736(16)30173-8. [Epub ahead of print]. Wen H, Baker JF. Vitamin D, immunoregulation, and rheumatoid arthritis. J Clin Rheumatol 2011;17(2):102–7. H. Takayanagi. Osteoimmunology and the efects of the immune system on bone. Nature Reviews Rheumatology 2009;5:667–76. N. J. Horwood, V. Kartsogiannis, J. M. W. Quinn, et al. Activated T lymphocytes support osteoclast formation in vitro. Biochemical and Biophysical Research Communications 1999;265(1):144–50. Y. Choi, K. M. Woo, S. H. Ko et al. Osteoclastogenesis is enhanced by activated B cells but suppressed by activated CD8+ T cells. European Journal of Immunology 2001;.31(7):2179–88. Acknowledgements: This work was supported by a Research Grant from the National Natural Science Foundation of China (no.81301532) and the Shanxi Science and Technology research projects of China (no.201603D321074). The authors thank Dr Alexis Ogdie for reviewing the manuscript. Disclosure of Interest: None declared